Studi Mengenai Anak Yang Mengalami Hambatan Perilaku Dan Emosi Yang Berfokus Pada Gejala Hiperaktif Dan Tunalaras - Mega Utami Imyansah; Rima Junita Putri; Yohana Dwi Putri; Nailah Assahira; Wismanto Wismanto (LPPM Politeknik Pratama, 2024)
Tunalaras and hyperactivity have different meanings. Hyperactive children tend to have the urge to do things excessively, have difficulty staying still, and are always active. Meanwhile, children with disabilities are children who experience chronic behavioral and social disorders. This study aims to analyze the behavior of children who experience behavioral and emotional barriers, focusing on symptoms of hyperactivity and impairment. The method used in this study is qualitative research using library research methods. Data was collected through a review of journals, books, and other sources of information relevant to the research topic. Data analysis is carried out using a descriptive approach with data reduction techniques, data analysis, and conclusions. The results showed that a child can be considered to have hyperactivity disorder and impaired he must show three main symptoms in his behavior, namely inattention, hyperactivity, and impulsivity.